Additive manufacturing and computed tomography of bio-inspired anchorage systems. Issue 3 (30th July 2018) - Mallett, S. D.; Matsumura, S.; David Frost, J.
Abstract : Using additive manufacturing, computer-assisted models can be rapidly transformed into physical objects. When combined with x-ray imaging, minimally attenuating 3D printed objects can allow for enhanced insight into soil processes, whether that be through the design of novel testing devices, prototypes, or soil surrogates. In the present study, this methodology is exploited to investigate the pullout mechanics of bio-inspired anchors. The purpose of this paper is twofold: 1) to demonstrate the value of the union of 3D printing and x-ray computed tomography (CT) technologies, and 2) to evaluate the effect of geometry on the pullout behaviour of plant root-inspired anchor elements. The results of the experimental investigations demonstrate how x-ray computed tomography was used to effectively capture the evolution of soil behaviour during the uplift of three unique 3D printed prototypes. The analysis of the soil response was completed from both a global perspective, through an interpretation of the force-displacement data, and a local perspective, through an image correlation investigation of image sets at sequential displacement increments. The results provide insight into not only the means to design a more optimized anchor element, but also the efficacy of additive manufacturing-assisted x-ray tomography in investigating geotechnical problems.